Loyalty of Green Tourist : Mediating Role of Satisfaction - Yuniati, Nining; Priyanto, Sony Heru; Suharti, Lieli; Kusuma, Linda (E-Journal of Tourism; Volume 7 Number 1 (March 2020)DO - 10.24922/eot.v7i1.54951, 2020)
The paper aims to test a research model of the mediating role of satisfaction in creating loyalty of green tourists. The importance of loyalty refers to a number of unique characteristics of green tourists such as being associated with the middle class, high spenders, staying longer than common tourists, high involvement, and tolerance. By using SEM a mediation test was carried out related to the position of customer satisfaction (GCS) in mediating its decision to buy in an environmentally friendly hotel (GP) and its loyalty (GCL). In short, to get loyal customers, services must be created in order to encourage customer satisfaction. Keywords: green hotel, green tourist, loyalty, purchasing, satisfaction